EFFECTIVENESS OF THE SHADOWING TECHNIQUE IN LEARNING THE MAHARAH OF KALAM SANTRI MANHALUN NABIGHIN ARABIC AND TAHFIDZ DORMITORY - Sahbudin, Faisal; Haq, Samsul (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
The purpose of this study is to find out the effectiveness of the Shadowing Technique in learning the Maharah of Kalam Santri Manhalun Nabighin Arabic and Tahfidz Dormitory. The research method used is pre-experimental design, using one experimental class. The sample used in this study is 13. The data collection technique uses a recorded oral test. The results of this study used a t-test to determine the difference between pretest and posttest results. The results of this study show that there is an increase in the maharah kalam of Santri Manhalun Nabighin Arabic and Tahfidz Dormitory. This can be proven by the results of the hypothesis test, which shows at a significance level of 5% tcal = 6.948 > ttable = 2.179. From these results, the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected).